Civil War Writing : New Perspectives on Iconic Texts - Cushman, Stephen, 1956-; Gallagher, Gary W. (Book collections on Project MUSE., 2019)
"In Civil War Writing: New Perspectives on Iconic Texts, editors Gary W. Gallagher and Stephen Cushman collect new scholarly essays which explore the significant texts about the American Civil War written by the people who lived through it, whether as civilians or combatants, southerners or northerners, women or men, blacks or whites. Several of the works discussed in the book, such as William Tecumseh Sherman's and Edward Porter Alexander's memoirs and Mary Chesnut's diary, will be familiar to many readers, but other works, including Charlotte Forten's diary and Loreta Velasquez's memoir, may not. In all cases, the contributors explore why these works resonate with audiences across different eras"--